Análisis de la pobreza: aspectos teóricos y su aplicación al caso argentino (1980-2000) - Santos, María Emma (Estudios económicos, 2002)
Análisis de la pobreza: aspectos teóricos y su aplicación al caso argentino (1980-2000)